Analisis perencanaan kesehatan oleh lembaga lembaga perencana kesehatan daerah (BAPPEDA Tingkat II dan Dinas Kesehatan Tingkat II) di Daerah Tingkat II Propinsi Daerah Istimewa Yogyakarta = Health planning analysis ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Background: Board of District Planning/I31)P (Bappeda Dati II) and District Health Office/ Dl-10 (Dinas Kesehatan Dati II) are two health planning institutions at district level within Yogyakarta Special Territory. Current nation showed that these institutions are lacking capacity. This can he seen from the total health budget of the year 1998/99 at district level, which is dominated by central share (-10 - 76 %). Additionally, there is inappropriate share of proportion between the total district budget t APBD 11) compared to the total district health budget (APBD II Kesehatan). District Health Budget (APBD II Kesehatan) in average only receives less than 3 ',I, of the total district budget (total APBD II). The purpose of this study was to analyze the existing capacity of health planning institutions, which would be categorized as internal and external capacity. and eventually propose recommendations, which match with the problem :wised. particularly in the light of the approaching district autonomy in 2001. Method: This study is an exploratory descriptive analysis, which uses qualitative method such as in-depth interview. structured observation and Focus Group Discussion. The subjects of the study included government employees at Bappeda Dad 11 (BDP) and Dinas Kesehatan Dali II (DI-10) from Kulonprogo District and Yogyakarta Municipal. who were influential in developing health plans at district/ municipal level. Results: The internal capacity of health planning institutions itt Kulonprogo and Yogyakarta Municipality was not adequate to perform a comprehensive health planning of an acceptable quality at district level. Some issues were raised, such as incoordination with related sectors. and the planning steps were not implemented in a logical sequence. This study also showed that external capacity of health planning institutions in Kulonprogo District and Yogyakarta Municipality was weak. The prohlem manilesis due to lack of ability of Bappeda Dati II in their eflOrts to develop an appropriate district budget to support the defined Priority Scale List in health sector. Conclusion: The result of this study indicates that during this period of anticipation l'or district autonomy. Bappeda Dati II and Dinas Kesehatan Dati II in Kulonprogo District and Yogyakarta District are insufficient for supporting decentralization.